Impact of the health insurance deregulation policy for cross-regional healthcare on hospitalization visits and expenses of patients with ischemic heart disease: an interrupted time series analysis - Yueying Cui; Xi Wang; Jiu Cheng; Yifei Wang; Huimin Yang; Ruihua Feng (Frontiers in Public Health)
BackgroundThe health insurance deregulation policy aimed to enhance healthcare accessibility by eliminating intra-provincial administrative hurdles. However, its impact on hospitalization patterns of high-burden chronic conditions like ischemic heart disease (IHD) remains unexamined.MethodsInterrupted time-series analysis (ITSA) was employed to evaluate weekly hospitalization visits and expenses for 8,522 IHD inpatients across three Hebei counties (January 2021–July 2023). Models assessed immediate and longitudinal changes post-policy, adjusting for autocorrelation and seasonal trends.ResultsPolicy implementation triggered an immediate 20.27 surge in weekly hospitalizations (p = 0.006), with sustained utilization unaffected (β3 = 0.17, p = 0.619). Per-visit hospitalization expenses maintained pre-deregulation policy declining trends (−126.71 CNY/week pre-policy vs. −32.04 CNY/week post-policy), despite a non-significant instantaneously increase by 478.43 (p = 0.723) in the first week following the implementation of this policy. Additionally, the health insurance deregulation policy reversed the weekly trend of insurance reimbursement costs per visit from decreasing (−81.98 CNY/week) to increasing trajectories (1.95 CNY/week, p = 0.004).ConclusionThe health insurance deregulation policy successfully expanded IHD care access without exacerbating financial burdens, demonstrating that administrative simplification can coexist with cost containment under concurrent payment reforms.